Kako je ime metodi? - Hladnik, Miran (Slavistična revija, 2001)
The author reflects on his own methodological profile, i.e, the literary criticism procedures that he has used since 1980, their foundation and place in the Slovene literary criticism. His approach to the literary system is non-selective and open to empirical methosds nad modern technology.
Keywords: history of literature; literarna kritika; literarna teorija; literarna zgodovina; literary criticism; literary theory; Slovene literature; slovenska književnost